Diagenetic controls on reservoir quality of tight sandstone: A case study of the Upper Triassic Yanchang formation Chang 7 sandstones, Ordos Basin, China (2018)
Through a range of petrological techniques, the petrology, diagenesis, pore characteristics, and controlling factors on the regional variations of reservoir quality of the Chang 7 sandstones were studied. These sandstones, mainly arkoses, lithic arkoses, and feldspathic litharenites, were deposited in a delta front and turbidites in semi-deep to deep lacustrine. The detrital constituents were controlled by the provenance and sedimentary condition, which resulted in a spatially variable composition; e.g., high biotite and feldspar contents in the northeast (NE) of the study area, and high contents of rock fragments, especially dolomite, matrix, and quartz in the southwest (SW). Diagenesis includes intense mechanical compaction, cementation, and dissolution of unstable minerals. Diagenetic minerals which were derived internally include quartz, ankerite, ferrous calcite, albite, illite, kaolinite, and chlorite. Thus the original sandstone composition hadfirm control over the development and distribution of cement. Mechanical compaction and late-stage cementations contribute to the porosity loss of sandstones of Chang7 member. The dissolution porosity in major sandstone, slightly higher than primary porosity is principally dependent on the accessibility of acid fluid. The high content of plastic component facilitated the reduction of primary porosity and limited the mineral dissolution. The best reservoir sandstones are found in W, and partly from NE, M districts, with porosity are primary. The relatively high textural maturity of these sandstones reduces the impact of compaction on primary pores, and commonly existed chlorite rims limited the precipitation of pore filling quartz and carbonate cementation in late stage.